2017
DOI: 10.1016/j.taap.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to three-dimensional printer emissions stimulates acute hypertension and microvascular dysfunction

Abstract: Fused deposition modeling (FDM™), or three-dimensional (3D) printing has become routine in industrial, occupational and domestic environments. We have recently reported that 3D printing emissions (3DPE) are complex mixtures, with a large ultrafine particulate matter component. We and others have reported that inhalation of xenobiotic particles in this size range is associated with an array of cardiovascular dysfunctions. Sprague-Dawley rats were exposed to 3DPE aerosols via nose-only exposure for ~3 hours. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 29 publications
1
43
2
Order By: Relevance
“…4 In an animal toxicology study, rats that inhaled ABS emissions from a desktop FFF 3-d printer developed acute hypertension. 5 At this point in time, it is unclear if these respiratory and cardiovascular endpoints are associated with inhalation of emitted particles, organic vapors, or both. Given these emerging reports of adverse health effects, there is a need to understand the magnitude and characteristics of emissions and exposures from AM processes in workplaces so that informed decisions can be made with regard to risk management.…”
Section: Introductionmentioning
confidence: 99%
“…4 In an animal toxicology study, rats that inhaled ABS emissions from a desktop FFF 3-d printer developed acute hypertension. 5 At this point in time, it is unclear if these respiratory and cardiovascular endpoints are associated with inhalation of emitted particles, organic vapors, or both. Given these emerging reports of adverse health effects, there is a need to understand the magnitude and characteristics of emissions and exposures from AM processes in workplaces so that informed decisions can be made with regard to risk management.…”
Section: Introductionmentioning
confidence: 99%
“…Personal breathing zone samples for metals and VOCs were collected at Facilities A and B only. Prior laboratory studies have reported iron, nickel, chromium, and zinc in particulate emissions from desktop-scale material extrusion printers using ABS and PL filaments [7], [21], [27]. As such, we used nanoparticle respiratory deposition (NRD, Zefon International, Inc., Ocala, FL, USA) samplers to collect metal-containing particles with diameters from about 15 to 300 nm [30].…”
Section: Methodsmentioning
confidence: 99%
“…In a survey of AM workers who primarily used material extrusion machines, 59% reported respiratory symptoms [6]. In an animal toxicology study, rats who inhaled ABS emissions from a material extrusion machine developed acute hypertension [7]. It is unclear if these respiratory and cardiovascular endpoints are associated with inhalation of airborne particles, organic vapors, or both.…”
Section: Introductionmentioning
confidence: 99%
“…RHD continues to maintain several research laboratories dedicated to conducting original inhalation exposure assessment research and providing support for field investigations by developing novel and innovative approaches for the sampling and analysis of chemical and biological agents. Recent examples of this research include development of methods for measuring diacetyl and 2,3-pentanedione in air, 68 and quaternary ammonium compounds in air and on surfaces, 69 assessing 3-dimensional printer emissions, 70 and characterizing fungi and fungal products in settled dust samples. 71…”
Section: Laboratory-based Studiesmentioning
confidence: 99%